Women and religion : a sociological analysis - Renavikar, Madhavi D. (Jaipur : Rawat Publications, 2003)
Study with reference to Maharashtra, India.
Includes statistical tables.
Includes bibliographical references (p. [331]-345) and index.
Keywords: Women and religion -- India -- Maharashtra; Hinduism and culture -- India -- Maharashtra; Women -- India -- Maharashtra -- Social conditions; Maharashtra (India) -- Religious life and customs